Differential sensitivities of physiologic races of microcyclus ulei to fungicides - Kai-Ming Zhang; Chee K H (Journal of Natural Rubber Research, 1986)
Benomyl, thiophanate methyl, chlorothalonil, and mancozeb were tested against Races 4, 6, 7 and 8 of Microcyclus ulei for inhibition of conidial germination, leaf disc infection, and field disease control. Races 6 and 8 were less sensitive to benomyl and thiophanate methyl than Races 4 and 7. Spraying benomyl (25 mg and 50 mg per litre) in the nursery gave satisfactory control of South American leaf blight on clones FX 2261 and FX 985 infected by Races 4 and 7 respectively, but not FX 3864 and FX 2804 infected by Races 6 and 8 respectively.
Keywords: Fungicides; Microcyclus ulei